The Analysis of Cultural Content in Two EFL Textbooks Used at SMA IT Iqra’ And SMKN 1 Bengkulu City - Muhammad Ibnu Mustofa; Feny Martina (Universitas Bengkulu, 2019)
The aims of this research were to find out how cultural dimensions were displayed, what culture was the most dominant, and the percentage of local culture in textbooks used at SMA IT IQRA? (Pathway to English) and SMK N1 Grade X (Bahasa Inggris by KEMENDIKBUD) Bengkulu. This research applied content analysis study with descriptive qualitative analysis. The procedures used in data collection were document review and observation. In analysing the data, the concept by Mile and Huberman was applied. The study revealed that from the two textbooks, there was a difference in terms of dominance in cultural types and dimensions. In Pathway to English, there was38 % items of aesthetic sense, 32% of pragmatic sense, and 26% of sociological sense. Semantic sense had the least representation which was only 4%. In cultural types, there was (50%) for target culture, 44% for local culture, and 6% for international culture. As for Bahasa Inggris by KEMENDIKBUD, there was 44% for asthetic sense, 25% for sociological sense, 22% for aesthetic sense, and 8% for semantic sense. Local culture has most items to occur, which reached 47 percent, followed by target culture which was 41%. The last is international culture with 11% of occurrence. It is highly recommendable that teachers apply the books with more cultural dimensions and types to hep students broaden their cultural knowledge and awareness.